2015
DOI: 10.1177/0894845315576372
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Employability, Emotional Exhaustion, and Turnover Intention

Abstract: In the boundaryless career era, employability is valued by both employees and employers. In this study, we investigated the effects of employability on employees’ strain and turnover intention in the Chinese setting, focusing on the moderating role of perceived career opportunity (PCO). We collected two-wave data from a sample of 214 employees over a three-month period. The results showed that employability was negatively related to emotional exhaustion and nonsignificantly related to turnover intention after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 51 publications
3
56
1
1
Order By: Relevance
“…university degree]) as control variables because these variables are potentially related to negative organization-related career shocks and/or job insecurity, and/or career optimism (Keim et al, 2014, Näswall and De Witte, 2003, Gunkel et al, 2010, Harney et al, 2018, Zheng et al, 2014. Specifically, these variables (e.g., education or leadership position) are theoretically and empirically linked to different career opportunities (Day, 2000, Lu et al, 2016, De Vos et al, 2009, and therefore might affect relations between career shocks and career optimism.…”
Section: Methodsmentioning
confidence: 99%
“…university degree]) as control variables because these variables are potentially related to negative organization-related career shocks and/or job insecurity, and/or career optimism (Keim et al, 2014, Näswall and De Witte, 2003, Gunkel et al, 2010, Harney et al, 2018, Zheng et al, 2014. Specifically, these variables (e.g., education or leadership position) are theoretically and empirically linked to different career opportunities (Day, 2000, Lu et al, 2016, De Vos et al, 2009, and therefore might affect relations between career shocks and career optimism.…”
Section: Methodsmentioning
confidence: 99%
“…The five-item Chinese version (Lu, Sun, & Du, 2016) of Rothwell and Arnold's (2007) employability scale was used to measure an employee's likelihood of securing and retaining a job. A six-point response scale was used, with high scores indicating high levels of employability.…”
Section: Employabilitymentioning
confidence: 99%
“…As the empirical research on employability and turnover intention remains limited and a few recent studies conducted in this domain have shown mixed results (Acikgoz, Sumer, & Sumer, 2016; Benson, 2006; De Cuyper, Mauno, Kinnunen, & Mäkikangas, 2011a; De Cuyper, Van der Heijden, & De Witte, 2011b; Lu, Sun, & Du, 2016; Rahman, Naqvi, & Ramay, 2008) we followed De Cuyper and De Witte (2011) to introduce two dimensions to employability: internal and external, both of which differ in scope and in focus of opportunities (De Vos, Forrier, Van der Heijden, & De Cuyper, 2017). Furthermore, this study advances previous research and responds to a recommendation by De Cuyper et al (2011a) to account for possible moderators in the indirect employability–turnover relationship through the introduction of perceived organization support and career orientation as possible moderating factors that might explain this complex relationship.…”
Section: Introductionmentioning
confidence: 99%